Effect of metformin on the human T98G glioblastoma multiforme cell line - GEPDİREMEN, ALİ AKÇAHAN; Ucbek, Ali; Ozunal, Zeynep Gunes; Uzun, Ozge; Gepdiremen, ALİ AKÇAHAN (My University, 2014)
Metformin is a guanidine derivative found in Galega officinalis that is commonly used to treat diabetes mellitus. The mechanism of action of metformin involves regulation of the adenosine monophosphate-activated protein kinase/mammalian target of rapamycin signaling pathway, which is implicated in the control of protein synthesis and cell proliferation. This led to the hypothesis that metformin reduces the risk of cancer and slows tumor growth. Thus, in the present study, the effectiveness of metformin as an antiglioma agent was evaluated using the human T98G glioblastoma multiforme cell line. The viability of the T98G cells was assessed using a 3-(4,5-dimethylthiazol-2-yL)-2,5-diphenyltetrazolium bromide assay. Apoptosis was monitored by measuring caspase-3 levels, as well as by terminal deoxynucleotidyl transferase dUTP nick end labeling and staining with acridine orange and ethidium bromide. The results demonstrate that metformin reduced cell viability and caused apoptotic morphological changes in the T98G cells. Furthermore, the caspase-3 levels in the metformin-treated T98G cells were higher than those in the control cells. Metformin induced apoptosis in the T98G cell line in a concentration-dependent manner. Metformin may provide an important contribution to the treatment of glioblastoma multiforme.